Caries detection and diagnosis methods: a narrative review (Research, Society and Development, 2020)
Dental caries is one of the most prevalent chronic diseases in people worldwide, individuals are susceptible to this disease at all stages of life. To review in the literature what tools are available for the diagnosis and detection of caries and its lesions. Data collection was performed at PubMed, between January 2019 and June 2020, with the keywords: “dental caries” AND “diagnostic” AND “ICDAS”, without language restriction or country of publication. Several detection methods were found, such as: ICDAS (International Caries Detection and Assessment System), Caries Assessment Spectrum and Treatment - CAST), DIAGNOdent® - LF; DIAGNOdent pen, CarieScan PRO (CP), VistaCam, DMF (Decayed – Missing – Filled - DMF) and others. The use of ICDAS in treatment recommendations for caries lesions varied between examiners. The use of an explorer in the evaluation of caries lesions has increased the validity and reliability of the decision on superficial cavitation. Decision-making about treatment can be influenced by the caries lesion detection and classification system. The research pointed out that there are variations between the studies and the use of the ICDAS system for caries. Conclusion: The ideal caries detection system should allow early diagnosis of caries at an early stage and improve decision-making in relation to an appropriate treatment plan.